Integrating Theories of Psychological Needs‐as‐Requirements and Psychological Needs‐as‐Motives: A Two Process Model. Issue 2 (February 2014) - Prentice, Mike; Halusic, Marc; Sheldon, Kennon M.
Abstract Two conceptions of psychological needs predominate within contemporary motivational science. Motive disposition theory conceives of needs as behavioral motives which direct behavior (needs‐as‐motives), while self‐determination theory conceives of needs as universally required experiences for optimal functioning (needs‐as‐requirements). Until recently, these perspectives on psychological needs have proceeded without much intersection, despite the fact that they address the same fundamental concept. Here we summarize the Two Process Model of Psychological Needs, which attempts to bridge these two conceptions. We argue that psychological needs are best defined as tendencies to seek out certain basic types of psychosocial experiences, to a somewhat varying extent across individuals, and to feel good and thrive when those basic experiences are obtained, to the same extent across individuals. We suggest that this definition allows a reconciliation of needs‐as‐motives and needs‐as‐requirements perspectives and a more consilient science of human motivation. Empirical support for the TPM is also summarized.